'There's not much demand for it': evaluating the concept of demand in Welsh-medium and bilingual provision in further education. Issue 7 (9th August 2022) - Davies, Laura Beth
ABSTRACT: This article explores the role of the concept of 'demand' in Welsh-medium education policy in Further Education and its effectiveness in increasing the number of learners studying through the medium of Welsh and bilingually. The research is based on a sample of four different areas across Wales, drawing on semi-structured interviews with staff in schools and Further Education colleges, and on focus groups with pupils in the final year of their statutory education, who are intending to pursue vocational subjects. The study identifies the principles underlying planning provision according to demand, and analyses the limitations of doing so. Using Bourdieu's concepts of linguistic habitus and the linguistic market, the article examines how planning according to demand fails to take into consideration the power context of Welsh and English, and the social expectations of the networks in which learners make linguistic choices. It argues that in order to increase the number of learners following Welsh-medium and bilingual provision in the FE sector in Wales, there is a need to reject the neoliberal discourse of choice and demand.